Experimental evolution of a pathogen confronted with innate immune memory increases variation in virulence. - Ana Korša; Moritz Baur; Nora K E Schulz; Jaime M Anaya-Rojas; Alexander Mellmann; Joachim Kurtz (PLoS Pathogens)
Understanding the drivers and mechanisms of virulence evolution is still a major goal of evolutionary biologists and epidemiologists. Theory predicts that the way virulence evolves depends on the balance between the benefits and costs it provides to pathogen fitness. Additionally, host responses to infections, such as resistance or tolerance, play a critical role in shaping virulence evolution. But, while the evolution of pathogens has been traditionally studied under the selection pressure of host adaptive immunity, less is known about their evolution when confronted to simpler and less effective forms of immunity such as immune priming. In this study, we used a well-established insect model for immune priming - red flour beetles and their bacterial pathogen Bacillus thuringiensis tenebrionis - to test how this form of innate immune memory drives the pathogen evolution. Through controlled experimental evolution of the pathogen in primed versus non-primed hosts, we found no change in average virulence after eight selection cycles in primed host. Nonetheless, we observed a notable rise in the variability of virulence, defined as the ability to kill hosts, among independent pathogen lines that evolved in primed hosts, and the bacteria were unable to develop resistance to host priming. Whole genome sequencing revealed increased activity in the bacterial mobilome (prophages and plasmids). Expression of the Cry toxin - a well-known virulence factor - was linked to evolved differences in copy number variation of the cry-carrying plasmid, though this did not correlate directly with virulence. These findings highlight that innate immune memory can drive variability in pathogen traits, which may favor adaptation to variable environments. This underscores the need to consider pathogen evolution in response to innate immune memory when applying these mechanisms in medicine, aquaculture, pest control, and insect mass production.